Analysis of DC bus bar dominant stray parameters based on equivalent calculation models. Issue 3 (29th November 2019) - He, Shaomin; Yang, Huan; Li, Guangzhuo; Hu, Sideng; He, Xiangning
Abstract : Purpose: This paper aims to analyze the dominant stray parameters of the DC bus bar and focus on weakening the influence of the stray parameters instead of reducing the value of the stray parameters in DC bus bar while switching. By finding the mechanisms to reduce the effects of stray parameters on switching transient, the simple and straightforward optimization methods could be given for the engineering designer. Design/methodology/approach: The investigations are focused on the equivalent circuit by segmented impedance evaluation in the low-frequency band and the energy propagation by wave impedance evaluation in the high frequency band. This paper proposes an equivalent impedance calculation model to locate the dominant stray parameters in the DC bus bar and takes the energy propagation characteristics using wave impedance into consideration, which can simplify the optimization design of DC bus bar. Findings: According to the equivalent circuit and electromagnetic field analysis, this paper proves the existence of the dominant stray parameters in DC bus bar that is widely used on high-power converters and certifies that not all the stray parameters in different areas of DC bus bar have the same effects on switching process, which can give a good guidance for the optimization design of DC bus bar. Originality/value: The positions of DC-link capacitors, resulting in only part of stray parameters in DC bus bar has more impact during switching, are significant to the DC bus bar optimization design. These stray parameters named dominant stray parameters in this paper play a leading role in the switching transient process. The area of DC bus bar, which is close to IGBTs and far from DC-link capacitors, contains the dominant stray parameters in the switching transient process. Therefore, the distance between DC-link capacitors and IGBTs should be shortened as much as possible. Based on the results, the efficiency for the DC bus bar optimization design could be improved by weakening the influence of the stray parameters, such as reducing the dominant stray parameters only. Therefore, it can save the cost and time of DC bus bar optimization design.